The effects of the intense laser field on bound states in GaxIn1−xNyAs1−y/GaAs single quantum well (2011)
ABSTRACT: We have investigated the effects of the intense laser field and nitrogen concentration on bound state energy levels in GaxIn1−xNyAs1−y/GaAs quantum well. The results show that both intense laser field and N-incorporation into the GaInNAs have strong influences on carrier localization. We hope that our results can stimulate further investigations of the related physics, as well as device applications of group-III nitrides.